Effects of Lactobacillus Casei Consumption on Inflammation Biomakers and Histological Changes in Selected Organs in Normal and Diabetic Rats. - Zarfeshani, Aida (2011)
The severity of diabetes mellitus often manifested by a progressive inflammatory biomarkers. Reducing the rate of the inflammation progression is one of the many measures to reduce complication of the disease. Many established evidences have suggested the beneficial effect of probiotic consumption on the progression of inflammatory bowel syndrome (IBS). In the present study, possible benefit of probiotics on inflammatory progression of diabeties mellitus (DM) is investigated. The present study employed two different approaches to induce hyperglycemia in adult Sprague-Dawley rats. The initial approach using high fructose diet (HFD), (21% w/v), was unable to induce satisfactorily hyperglycemia in the animal. Chemical induction using streptozotocin (STZ), ( 50 mg/ kg body weight) induced hyperglycemia in all animals injected. Rats in both batches were divided into groups. A non-diabetic group (ND), a non-treated group with a standard diet (NT) and two diabetic groups which were treated with 109 cfu/ml/day (LCI/DLCI) and 1011 cfu/ml/day (LC2/DLC2) of self-cultured Lactobacillus casei strain Shirota. The pribiotic L.cS was gavaged for three consecutive weeks. Blood was collected through the orbital venous plexus to measure circulating C-reactive protein (CRP), interleukin-6 (IL-6) and interleukin-4 (IL-4) as the inflammatory biomarkers. The results have shown no significant difference in blood glucose level of L.cS fed rats compared with non-treated group (p>0.05). Both doses of L.cS were observed to induce lower CRP production after three weeks of administration compared to the diabetic control group. Interleukin-6 was found to be decreased but only at higher dose (1011 cfu/ml) of the L.cS which was comparable with the level that was observed in the non-diabetic group at the end of the study duration. Interleukin-4 level was found to be significantly decreased in all treated and the diabetic control group, but was observed to be higher in the normal group. Data from the three inflammatory biomarkers suggested that probiotic L.cS has the potential to improve inflammatory status among STZ-induced rats. Histological study of the pancreas showed a huge damage of the Langerhans islets in STZ induced rats. In addition, foamy cells were found in the kidney cortex of the STZ induced rats. Colon condition was similar among all groups. Inflammatory invasion was evidenced in the liver where the presence of neutrophils could be clearly seen in the non-treated group. Treatment with the L.cS observed a significant reduction in the invasiveness of the neutrophils which highly indicates decreased levels of inflammation by the probiotics. The results of this study indicate that Lactobacillus casei strain Shirota, possess an ability to reduce inflammatory biomarkers hence complication caused by inflammation in DM.